2014
DOI: 10.3109/03630269.2014.944915
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of β-Thalassemia Mutations in Hatay, Turkey: Reporting Three New Mutations

Abstract: β-Thalassemia (β-thal) is an important health problem in Hatay, Southern Turkey, because of its high carrier frequency and the frequency of consanguinity. The aim of this study was to reveal the spectrum of β-thal mutations and to provide a foundation for prenatal genetic testing that will be a part of an effective prevention program for β-thal disease in Hatay. We determined the spectrum of β-thal mutations in 93 unrelated affected patients. Using a direct sequencing method, we identified a large number of β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The wide molecular heterogeneity of Turkish thalassemic subjects has been confirmed by this registry. The most common seven mutations accounted for less than 80% of all thalassemia alleles, consistent with previous reports from Turkey [ 15 , 16 , 17 , 18 , 19 , 20 ]. The IVS-I-110(G->A) substitution was the most common defect with a frequency of 47% within all b-thalassemia alleles in the cohort.…”
Section: Discussionsupporting
confidence: 91%
“…The wide molecular heterogeneity of Turkish thalassemic subjects has been confirmed by this registry. The most common seven mutations accounted for less than 80% of all thalassemia alleles, consistent with previous reports from Turkey [ 15 , 16 , 17 , 18 , 19 , 20 ]. The IVS-I-110(G->A) substitution was the most common defect with a frequency of 47% within all b-thalassemia alleles in the cohort.…”
Section: Discussionsupporting
confidence: 91%
“…The most common mutations were: IVS-I-110 (G > A), IVS-I-6 (T > C), IVS-I-1 (G > A), frameshift codon (FSC)8(ÀAA), codon 39 (C > T), and IVS-II-745 (C > G). They reported that many Syrian and Iraqi immigrants presented with a prevalence of thalassemia traits that were different from other studies [2]. β-Thalassemia is caused by more than 300 different β-globin chains (http:// www.ithanet.eu/db/ithagenes;http://globin.bx.psu.edu/hbvar) but only about 40 account for 90% or more of β-thalassemia cases worldwide [6].…”
Section: Molecular Diagnosis Of β-Thalassemiamentioning
confidence: 92%
“…βThalassemia in the group of thalassemia syndromes is molecularly heterogeneous. Especially, genetic testing can provide important information fordiagnosis,treatment,andprevention.There are some limitations to genetic testing in all types of thalassemia; the most important issue is to find the right patient on which to perform genetic testing [2].…”
Section: Introductionmentioning
confidence: 99%
“…The IVS-I-6 (T→C) mutation is one of the most common causes of β-thalassemia among individuals of Mediterranean and Middle Eastern ancestry [39,40]. Its high incidence has been reported among populations from Portugal [41]; Spain [42,43]; Albania [44]; the region of former Yugoslavia [45,46,47,48]; Greece [49,50,51,52]; Algeria [53]; Egypt [54]; Palestine [55,56]; Lebanon [57]; Syria [58,59]; Cyprus [60]; Turkey [61,62,63,64,65]; Saudi Arabia [66,67]; Iraq [68,69,70,71]; Iran [72,73,74]; and elsewhere. It results from a base substitution close to the 5′ splice junction, between exon I and intron I, and within a conserved consensus sequence, interfering with mRNA splicing and, consequently, reducing its efficiency.…”
Section: Discussionmentioning
confidence: 99%